Kualitatif Interpretatif Merleau-Ponty Dalam Fenomena Perkembangan Fashion Remaja Di Indonesia - Yassar, Fauzan Waly; Kartadinata, Fathurahman; Rizkia, Reza (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2020)
Hypebeast is an online-based digital media that focuses on the fashion of young people in streetwear style. Hypebeast also produces magazines that discuss lifestyle or trends in urban areas. With the power of social media, Marketing activities could be well conducted by Instagram. @hypebeast account became a phenomenon in the style of streetwear dress especially among young people even though some the products they uploaded on their Instagram account were premium or somewhat expensive. A qualitative interpretive approach aims to find out the role of the phenomenon of the use of Instagram @hypebeast account in the development of fashion in Indonesia. In addition, this study also aims to find out what factors make young people in Indonesia render @hypebeast as a standard to dressing up. This research refers to the theory of perception phenomenology by Maurice Marleau-Ponty. Primary data in this study were obtained by conducting interviews with 10 sources. The results of the research obtained differ from each source. Perception or what is meant about Instagram @hypebeast account can be distinguished from the background of the source. Students interpret the account as a fashion account that uploads the latest information about trends in the fashion world of streetwear style. While practitioners interpret the account is not just fashion but broader that is an attractive lifestyle which then leads to sales of Hypebeast magazine sales.